Review: Die Schmetterlinge Baden-Württembergs - Mikkola, Kauri (Entomologica Fennica, 2000)
Ebert, Günter (ed.) 1997, 1997 & 1998: Die Schmetterlinge Baden-Württembergs. Bände 5-7. Sesiidae, Arctiidae, Noctuidae. 575 + 622 + 582 pp., 400 + 512 + 483 colour photographs, 360 + 433 + 329 diagrams and drawings, and 133 + 187 + 170 distribution maps. Verlag Eugen Ulmer. Stuttgart. ISBN 3-8001-3481-0, 3-8001-3482-9, 3-8001-3500-0. Price: Ca. FIM 480,-/part.